1997
DOI: 10.1620/tjem.181.471
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Blocking Actions of the Aminoglycoside Antibiotics Sisomicin and Micronomicin in the Rabbit.

Abstract: The neuromuscular blocking actions of sisomicin sulfate (SISO), micronomicin sulfate (MCR) and d-tubocurarine (dTc) were studied in 20 rabbits anesthetized with halothane. The i.v. administration of SISO 20-40 mg/kg, MCR 40-80 mg/kg or dTc 0.1-0.3 mg/kg resulted in dose-dependent decreases in twitch tension. The ED50s for SISO, MCR and dTc were 23.5, 58.2 and 0.2 mg/kg, respectively. SISO- and MCR-induced neuromuscular blockade was partially antagonized by neostigmine or by calcium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Previous reported studies indicated that the majority of animals entered neuromuscular paralysis after high doses of aminoglycosides [282,283,403]. In our study, we assumed 70 % of the animals would enter neuromuscular paralysis after ultra-high doses of aminoglycosides.…”
Section: Ata Analysismentioning
confidence: 82%
See 4 more Smart Citations
“…Previous reported studies indicated that the majority of animals entered neuromuscular paralysis after high doses of aminoglycosides [282,283,403]. In our study, we assumed 70 % of the animals would enter neuromuscular paralysis after ultra-high doses of aminoglycosides.…”
Section: Ata Analysismentioning
confidence: 82%
“…The occurrence of neuromuscular paralysis and respiratory depression after high doses of aminoglycosides has previously been reported [282,283,434]. In our invasive, short-term study, we wanted to determine if the animals enter neuromuscular paralysis and survive when supported by ventilator for the duration of paralysis.…”
Section: Ata Analysismentioning
confidence: 97%
See 3 more Smart Citations